Pd-nanodot decorated MoS2 nanosheets as a highly efficient photocatalyst for the visible-light-induced Suzuki–Miyaura coupling reaction. Issue 47 (23rd November 2017) - Shin, Hyeon Ho; Kang, Eunmi; Park, Haeli; Han, Taejun; Lee, Chul-Ho; Lim, Dong-Kwon
Abstract : The incorporation of MoS2 nanosheets with Pd nanodots is a promising way for promoting the visible-light-induced C–C coupling reaction. Abstract : In this work, we demonstrate that the incorporation of MoS2 nanosheets with Pd nanodots is a promising way for promoting the visible-light-induced Suzuki–Miyaura C–C coupling reaction. The MoS2 nanosheets decorated with Pd nanodots showed very high photocatalytic activity. The turnover frequency for the biphenyl product was >1600 h −1 even under sunlight illumination at room temperature. Mechanistic studies show that the high catalytic activity originated from the efficient electron–hole pair generation mechanism of MoS2 under visible-light illumination instead of purely thermal effects.